Instrumentasi Hukum Ham, Pembentukan Lembaga Perlindungan Ham di Indonesia dan Peran mahkamah Konstitusi - M. Syafi’ie (Jurnal Konstitusi, 2016)
Post-reform occurs instrumentation very progressive human rights law. Assessment, extraction, creation of new legal dimension of human rights take place so quickly. Many international conventions that have been ratified. At the same time, the protection of human rights organizations, both national and international are also emerging. The fall of the Orde Baru in the perspective some intellectual say as a  sign of the receipt of the universalism of human rights in Indonesia. However, the substance of human rights law is made progressively still have many problems. The same is true of human rights protection institutions that have weaknesses, and tend to be attenuated. Among the many human rights agencies that overlap and do not go for the synergistic promotion of human rights in Indonesia. In that context, the Constitutional Court as the guardian of the constitution and is one of the human rights protector is expected to correct the errors of substance that are contrary to constitution and againt the human   rights.